2012
DOI: 10.3109/14767058.2012.685788
|View full text |Cite
|
Sign up to set email alerts
|

Pre-discharge iron status and its determinants in premature infants

Abstract: Iron status at 35 weeks PMA is extremely variable and is predicted by prior erythrocyte transfusions or net erythrocyte balance in premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The summary of the most relevant characteristics of the randomized and non-randomized studies included are shown in Table 3 and Table 4, respectively. Out of the 16 studies included, four were conducted in India [24,25,31,35], three were carried out in the Netherlands [30,32,33], four were performed in Sweden [26,27,28,29], three in the USA [36,38,39], one in Japan [37], and one in Brazil [34]; these studies were published between 2009 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The summary of the most relevant characteristics of the randomized and non-randomized studies included are shown in Table 3 and Table 4, respectively. Out of the 16 studies included, four were conducted in India [24,25,31,35], three were carried out in the Netherlands [30,32,33], four were performed in Sweden [26,27,28,29], three in the USA [36,38,39], one in Japan [37], and one in Brazil [34]; these studies were published between 2009 and 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the randomization, this review includes six randomized studies [24,25,26,27,28,29] (being [26,27,28,29] results from the same original cohort) and 10 non-randomized studies [30,31,32,33,34,35,36,37,38,39]. Four of these studies were double-blind [26,27,28,29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total body iron content, haemoglobin and ferritin concentrations are lower in pre-term infants (Halliday et al 1984;Singla et al 1985;Lackmann et al 1998), even in late pre-term infants born ≥34 weeks' gestational age (Ozdemir et al 2013;Yamada & Leone 2014). Between 20% and 50% of pre-term infants are either born iron deficient or will become deficient in early infancy (Amin et al 2010;Berglund et al 2010;Amin et al 2012;Uijterschout et al 2015;Akkermans et al 2016), with rates of 80-85% reported in pre-term infants exclusively breastfed or receiving inappropriate iron supplementation (Iwai et al 1986;Hall et al 1993).…”
Section: Prematurity and Low Birthweightmentioning
confidence: 99%